“Diseño de una máquina fibradora para plásticos de polietileno de baja densidad”. - Toapanta Cajahuishca, Diego Geovanny (2022)
The present study allows to establish the manufacturing procedure of a fibrous accessory that was adapted to an extrusion equipment with test characteristics for LDPE type plastic materials, as a manufacturing alternative in small production scales, especially in projection with recycled materials. The development of the proposal has been directed under the basic principle of the design steps (determination of the functional structure, scope, conceptualization, dimensional design, detailed design, planning of the manufacturing technology), which has been possible to develop with the help of various methods (experimental, systemic, calculation and others) and techniques (Pugh, surveys, interviews, others) that have facilitated the consolidation in the decision making through the various quantitative and qualitative assessments in obtaining the engineering as well as the equipment in its tangible form. Some of the most relevant results constitute the adequate coupling for the connection between the extruder machine and the fibrating machine, of this last one the dimensioning of each one of the pieces that would conform part of the machinery was carried out in this study and the calculations of the mechanical, thermal, electrical and control systems were proposed in order to guarantee a high reliability at the moment of the implementation. It is also relevant to mention that experimentally the temperature variable is maintained in ranges between 270°C and 315°C, and in the disk between 315°C to 350°C, temperatures that allow to sustain the liquid state of the plastic material, also the use of the dimmer as an alternative for the variation of the speed in single-phase motors allows that the speed of rotation of the motor is in variable ranges and the experimentation of the speed and thickness of the fiber is possible, which is proposed to be analyzed in future works.